Addressing racial disparities in COVID-19 compliance: A community-driven approach using the theory of planned behavior - Florent Nkouaga (Advances in Medicine, Psychology, and Public Health)
Introduction: The COVID-19 pandemic has highlighted significant racial and ethnic disparities in health outcomes and access to care. This study aims to explore the factors influencing public health compliance across different racial groups in the United States, utilizing the Theory of Planned Behavior (TPB) as a guiding framework. Methods: Data were drawn from the 2021 African American COVID-19 Vaccine Poll, which surveyed 12,887 adults from various racial and ethnic backgrounds between May and July 2021. A weighted Ordinary Least Squares regression analysis was employed to examine the relationship between TPB constructs—attitudes, subjective norms, and perceived behavioral control—and public health compliance, controlling for demographic variables and partisanship. Results: TPB constructs were significant predictors of compliance across all racial groups, though their influence varied. Attitudes toward COVID-19 had the strongest impact on compliance among White individuals and the weakest among Black individuals. Trust in health institutions (subjective norms) was consistently linked to higher compliance across all groups. Perceived behavioral control, particularly health access, was a significant predictor for most groups except Asian Americans. Partisanship significantly influenced compliance, especially among Black individuals and Latinos. Universal demographic predictors of compliance included being female and older age. Conclusion: This study uncovers a complex interaction between psychological, social, and demographic factors in shaping public health compliance during the COVID-19 pandemic. The findings highlight the necessity for tailored, culturally sensitive interventions to enhance public health compliance and address racial disparities in health outcomes.